2021
DOI: 10.11591/ijere.v10i3.21703
|View full text |Cite
|
Sign up to set email alerts
|

Students’ knowledge and attitudes toward basic life support

Abstract: <span lang="EN-US">Students spend a significant proportion of their day in colleges and healthcare facilities where they might experience medical emergencies, or unexpected accidents, that occur in these places. Nursing students are expected to play a key role in performing basic life support. This study is to evaluate knowledge, attitudes and training status with regard to basic life support (BLS). An online cross-sectional survey was conducted in Taif University, Saudi Arabia. 170 students agreed to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Studies such as those conducted at Taif Medical University in Saudi Arabia showed a low level of BLS awareness among 5th and 6th year medical students. This study showed that only 25 (12.8%) out of 196 participating students had adequate BLS knowledge and no student had excellent BLS knowledge 5 . The study by Vausevan et al in India evaluated medical and nursing students, showing that 3.7% of medical students and 17.4% nursing students have good BLS knowledge.…”
Section: Introductionmentioning
confidence: 71%
“…Studies such as those conducted at Taif Medical University in Saudi Arabia showed a low level of BLS awareness among 5th and 6th year medical students. This study showed that only 25 (12.8%) out of 196 participating students had adequate BLS knowledge and no student had excellent BLS knowledge 5 . The study by Vausevan et al in India evaluated medical and nursing students, showing that 3.7% of medical students and 17.4% nursing students have good BLS knowledge.…”
Section: Introductionmentioning
confidence: 71%
“…The goal of Alfakey study in Saudi Arabia was to evaluate students BLS knowledge, attitudes, and training status. She came to the conclusion that trained students had superior knowledge, skills, and attitudes to untrained students [ 16 ]. According to a study by Babar I in Pakistan, the general level of awareness among medical professionals is incredibly low, despite the fact that doctors have a greater understanding of BLS than dentists and nurses do [ 17 ].…”
Section: Discussionmentioning
confidence: 99%